Can Islamic Banking be an Alternative to Conventional Banking? A Survey on the Opinion of Depositors in Bangladesh - Md Atiqul Islam; Noor-E-Sabiha Noor-E-Sabiha; Farhad Hossain (Tazkia Islamic Finance and Business Review, 2024)
Given its distinct principles of banking operation, a general concern of research on Islamic finance is whether the Islamic banking is an alternative approach to the conventional banking. In an attempt to address the concern, this study aims to survey depositors’ reviews on product and service of their Islamic banks (IB). A respondent group of 395 depositors is selected for the survey from different IBs in Rajshahi city of Bangladesh. The Likert scale approach and data visualization method are used to analyse the depositors’ opinion and survey findings respectively. Around 51 percent of the total respondents are operating deposit accounts in both Islamic and conventional banks. This survey finds that, the depositors highly value the fundamental principle, prompt service facility, efficient customer management services and business reputation while selecting the Islamic banking as a preferred banking approach. However, to be a viable alternative and satisfy their depositors, IBs need to improve the transparency factor in investment risk and ensure effective management of banking services. This study has practical implications for Islamic financial institutions operating in Bangladesh.